A shared battle against cancer: overcoming screening uptake differences within European countries. (30th September 2020) - Villani, L; Riccardi, M T; Barbara, A; Sabetta, T; Nurchis, M C; Sabetta, A; Solipaca, A; Ricciardi, W
Abstract: Cancer is the second leading cause of dead in Europe and it is responsible of more than 30% of all deaths. For this reason, European Union (EU) identified the battle against cancer as a priority for the European Research Program 2021-2027.About 40% of total deaths for cancers could be prevented with screening.Validated screening test are available for breast (BC), cervical (CC) and colorectal cancers (CRC). In 2003 the Recommendation of the European Council indicated the right timing and the population target but, nowadays, the percentage of screening within EU is low and consistent differences persist among States.In 2020 there are still countries that don't have population-based screening programs. Last data available for all 28 EU countries are referred to 2014. Data were retrieved from "Osservasalute" reports and Global Burden of Disease database.Pearson test and a paired t test were used to describe correlation between mortality and screening coverage rates. In 2014 the mean percentage of screening was 70.7% for CC, 68.7% for BC and 31.3% for CRC and the mean of mortality rate was of 2.1, 10.4 and 17.2 for 100, 000, respectively.The rate of mortality did not change significantly in 2017 (2, 10 and 16 for 100, 000 respectively).The median coverage is 67 for BC [IR: 43-91], 21.4 for CRC [IR: -3-46] and 70.6 for CC [IR: 54-87]. Pearson test resulted in a negative correlation for all three cancers equal to -0.045, -0.060 and -0.561, respectively.A higher adherence to screening programs is significantly associated to lower mortality rates in all the three types of cancer (p < 0.01). Even if many factors determine the rate of cancer mortality, screening represents the best method to early diagnosis and treatment.Up-to-date data are needed to correctly monitor progress towards the common goal of reaching the entire target population with screenings.A strong leadership at international level is necessary to improve screening programs all over EU and support screening campaigns. Key messages: Screening is one of the most efficient and life-saving way to prevent cancer. It is needed to improve screening adherence through population-based programmes both at international and national level. Last data available for all EU countries are referred to 2014. It is necessary to update the data in order to enhance the understanding of screening efficiency.